Evolution of wage inequality in India (1983-2017): The role of occupational task content - Saloni Khurana; Kanika Mahajan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
We examine data for urban workers in the non-agricultural sector across three decades, 1983-2017, and find that earnings inequality increased during 1983-2004, was largely stable during 2004-11, and decreased during 2011-17. We explore whether decline in routine jobs and change in demand for skills has shaped evolution of earnings inequality in India. We rule out earnings polarization as an explanation for rising earnings inequality during 1983-2004, and then use Shapley and recentred influence functions (RIF) decomposition methods to decompose the change in Gini into the contribution from change in worker demographics and routine task intensity and the accompanying changes in returns to these characteristics. Our results show that changes in returns to education and routine task intensity explain a small part of the trends in wage inequality. Hence, in the Indian context, institutional factors may have played a bigger role in shaping wage inequality.
Keywords: D63; J21; J24; 330; skills; tasks; earnings inequality; decomposition; India